2011
DOI: 10.1042/bst20110669
|View full text |Cite
|
Sign up to set email alerts
|

Nesprin-3: a versatile connector between the nucleus and the cytoskeleton

Abstract: The cytoskeleton is connected to the nuclear interior by LINC (linker of nucleoskeleton and cytoskeleton) complexes located in the nuclear envelope. These complexes consist of SUN proteins and nesprins present in the inner and outer nuclear membrane respectively. Whereas SUN proteins can bind the nuclear lamina, members of the nesprin protein family connect the nucleus to different components of the cytoskeleton. Nesprin-1 and -2 can establish a direct link with actin filaments, whereas nesprin-4 associates in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 50 publications
1
41
0
Order By: Relevance
“…This points to the existence of topological borders of the perinuclear region, which we formally call the perinucleus . This is not inconsistent with the previous work of Ketema and Sonnenberg25, who demonstrated that a perinuclear infrastructure includes nesprins and plectins that form, in part, an indirect protein link of the nucleus to the plasma membrane.…”
Section: Discussionsupporting
confidence: 61%
“…This points to the existence of topological borders of the perinuclear region, which we formally call the perinucleus . This is not inconsistent with the previous work of Ketema and Sonnenberg25, who demonstrated that a perinuclear infrastructure includes nesprins and plectins that form, in part, an indirect protein link of the nucleus to the plasma membrane.…”
Section: Discussionsupporting
confidence: 61%
“…One way how P1 accomplishes its task is by interacting with the ONMspanning protein nesprin-3, which in turn binds to proteins spanning the inner nuclear membrane, establishing a connection between the IF cytoskeleton and the nuclear envelope [54]. This axis might additionally be connected to the actin cytoskeleton via torsinA [55].…”
Section: If Anchorage At the Nucleus Mitochondria And Sarcomeresmentioning
confidence: 99%
“…It was thus not surprising to learn that nesprin-3 connects to the microtubules via the cytoskeletal cross-linkers BPAG1 (bullous pemphigoid antigen 1) (isoform from the dystonin gene; belongs to plakin protein family) and MACF1 (microtubule-actin cross-linking factor 1) [17], nesprin-4 to the molecular motor kinesin 1, and nesprin -1/2 to dynein. It was established long ago that the ER network (a continuation of the ONM) lies alongside the microtubule network [18] and thus one might expect to find that INM/ONM proteins also associate with microtubules.…”
Section: Nucleocytoplasmic Connectionsmentioning
confidence: 99%
“…However, with the likelihood of further LINC components remaining to be identified and with the number of nesprin family genes/isoforms seeming to be exponentially growing, there is clearly much to learn about the functionality of nucleocytoskeletal connections. Indeed, nesprin-3 appears to play a more passive role than nesprin-1/-2, since it stabilizes nuclear anchorage, rather than orchestrating it [17].…”
Section: Nucleocytoplasmic Connectionsmentioning
confidence: 99%